All inorganic and transparent ITO/boehmite/ITO structure by one-step synthesis method for flexible memristor. (December 2021) - Duan, Weijie
Highlights: A boehmite layer was fabricated at low temperature by one-step solution method. An all inorganic and all transparent ITO/boehmite/ITO stacked structure was fabricated for flexible memristor. The device showed satisfied electrical characteristics and mechanical properties. This work finds a new way to develop flexible memory devices and wearable electronics. Abstract: In this work, an ITO/boehmite layer/ITO-stacked structure was fabricated at low temperature for transparent flexible memristor. Typical and reproducible bipolar switching behavior was easily obtained under applied bias. The resistive switching behaviors with satisfied electrical reliability such as retention, endurance and mechanical characteristics were all exhibited at different bending angles. The switching mechanism was considered to be related to the movement of H + in boehmite layer. This low temperature processed, all inorganic and transparent flexible device provides a feasible way to develop new type of information devices and wearable electronics.